Modulation of Dilp2 and Dilp5 Gene Expression by Pirdot Leaf Extract (Saurauia vulcani Korth.) in Drosophila melanogaster Hyperglycemia Model: A Literature Review - Simamora, Rizka Amini; Widjaja, Sry Suryani; Rusdiana (International Journal of Ecophysiology, 2025)
Hyperglycemia is a pathological condition caused by impaired glucose metabolism that contributes significantly to the development of diabetes mellitus. The use of medicinal plants such as pirdot leaves (Saurauia vulcani Korth.) as an alternative therapy has become a focus due to their bioactive compounds with antihyperglycemic properties. This article presents a literature review on the potential of pirdot leaf ethanol extract in modulating the expression of Dilp2 and Dilp5 genes in the Drosophila melanogaster hyperglycemia model. Drosophila melanogaster was chosen as a model organism because it has insulin signaling pathways homologous to humans and produces insulin-like peptides (DILPs), including Dilp2 and Dilp5, which play a crucial role in glucose regulation and energy metabolism. A high-sugar diet in this organism has been shown to disrupt glucose homeostasis and affect the expression of Dilp2 and Dilp5 genes. Pirdot leaf extract has been shown in vivo in mouse models to lower blood glucose levels and exhibit regenerative activity toward pancreatic cells. Although no direct studies have been conducted on the effects of pirdot extract on gene expression in Drosophila, previous studies indicate that plant compounds can influence metabolic pathways at the molecular level. Therefore, further research using Drosophila melanogaster is important to evaluate the potential of pirdot extract in gene expression-based hyperglycemia therapy.